Dystrofia polimorficzna tylna rogówki – opis przypadku - Nowińska, Anna; Wylęgała, Edward; Dobrowolski, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Posterior polymorphous corneal dystrophy (PPCD) is a rare, bilateral, congenital disorder. It affects endothelial cells and Descemet’s membrane. Slit lamp examination of PPCD shows characteristic bilateral endothelial bands, vesicles, and polymorphous opacities at the level of Descemet’s membrane and endothelium, which can be accompanied by iridocorneal peripheral adhesions, iris atrophy, and corectopia. The clinical phenotype of PPCD can vary from relatively benign Descemet’s thickening to severe progression towards vision loss from corneal edema or consecutive glaucoma. We present a case report of a 7-years old male patient with left eye corneal edema. Diagnosis of PPCD is made by slit-lam examination accompanied by anterior segment optical coherence tomography (AS OCT), and specular microscopy examination. Examination also revealed corneal changes in left eye of 32-years old patient’s mother.